Rites of passage from a gender perspective in Surfacing by Margaret Atwood - Sánchez, María Victoria (2015)
As readers, every time we take a book in our hands, we sink into an act of reading that invites us to think about what the text suggests but remains uncovered. Sometimes, those hidden messages make us reflect upon the links that exist between people and literature. The decision of having chosen the topic we are going to deal with in this work responds to the notion that Margaret Atwood’s narrative reflects a bond between the writer and her surroundings: she is the expression of her time. This study intends to analyze the novel Surfacing (1972) by Margaret Atwood. Our main interest lies in the journey that the main character takes from the city to her birthplace, which lasts seven days. The entire journey is permeated by a rite of passage that entails not only the ´surfacing´ of the main character but also the possibility of analyzing her voice as a voice of the subaltern, somebody who can speak but cannot be heard. In this way, Atwood presents a character that throughout her past and present becomes the voice of a whole generation. This work intends to address the following hypothesis: Within a historical-cultural framework signaled by a proliferation of gender studies, Surfacing by Atwood places women as the voice of the subaltern. Its main character is driven by a search of he own identity which entails a rite of passage. She begins a journey towards the ¨surfacing¨ of a new historic and metaphysical being. A lot of questions can be raised from this hypothesis; however, the ones that concern us are: Does Atwood’s main character represent a voice of the subaltern? Does the environment in the story work as a catalyst in the rite of passage? How is the rite of passage represented? And where does this rite lead us to? All these questions, and many others that are going to be referred to in this study, are intended to guide us towards the analyses of Atwood’s novel from an innovative perspective.